2008
DOI: 10.1017/s1743921308026495
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Hydrodynamical Studies of Irradiated Atmospheres

Abstract: Abstract. Transiting planets provide a unique opportunity to study the atmospheres of extrasolar planets. Radiative hydrodynamical models of the atmosphere provide a crucial link between the physical characteristics of the atmosphere and the observed properties. Here I present results from 3D simulations which solve the full Navier-Stokes equations coupled to a flux-limited diffusion treatment of radiation transfer. Variations in opacity amongst models leads to a variation in the temperature differential acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…prevailing circumplanetary flows) to be comparable in size with the horizontal extent of the atmosphere. Despite the exotic nature of the flow regime, the adaptation of GCMs to hot Jupiters has met with success as, for example, several models have been able to demonstrate that offsets in the hot spot are consistent with redistribution from zonal (longitudinal direction) winds (Showman et al 2009;Dobbs-Dixon & Lin 2008;Dobbs-Dixon 2009). The progress of the modelling has been reviewed in Showman et al (2008 and a useful summary of the different approaches taken can be found in Dobbs-Dixon & Agol (2013).…”
Section: Introductionmentioning
confidence: 99%
“…prevailing circumplanetary flows) to be comparable in size with the horizontal extent of the atmosphere. Despite the exotic nature of the flow regime, the adaptation of GCMs to hot Jupiters has met with success as, for example, several models have been able to demonstrate that offsets in the hot spot are consistent with redistribution from zonal (longitudinal direction) winds (Showman et al 2009;Dobbs-Dixon & Lin 2008;Dobbs-Dixon 2009). The progress of the modelling has been reviewed in Showman et al (2008 and a useful summary of the different approaches taken can be found in Dobbs-Dixon & Agol (2013).…”
Section: Introductionmentioning
confidence: 99%